CaMYBA–CaMYC–CaTTG1 complex activates the transcription of anthocyanin synthesis structural genes and regulates anthocyanin accumulation in pepper (Capsicum annuum L.) leaves - Ma, Xiaowei; Liang, Guangbo; Xu, Ziqian; Lin, Chenwei; Zhu, Biao (Frontiers in Plant Science, 2025)
Anthocyanins are flavonoid-derived metabolites that contribute to plant and human health. At present, few studies have studied the biosynthesis and accumulation mechanism of anthocyanins in pepper leaves. The role of CaMYBA–CaMYC–CaTTG1 complex in anthocyanin biosynthesis in pepper leaves was studied. Yeast two-hybrid and dual-luciferase experiments showed that CaMYBA, CaMYC, and CaTTG1 could form an MYB–bHLH–WD40 (MBW) complex. They also have transcriptional activation on the anthocyanin synthesis structural genes CaCHS, CaCHI, CaF3H, CaF3′5′H, CaANS, CaDFR, and CaUFGT. Silencing CaMYBA or CaMYC could decrease the content of anthocyanin in pepper leaves. Transient overexpression of CaMYBA in tobacco indicated that CaMYBA determines the function of an MBW complex. Further analysis showed that CaMYBA could activate the expression of CaMYC by binding to its promoter. Overall, our study expands the understanding of the regulatory mechanism of anthocyanin synthesis in pepper leaves and has important significance for creating more pepper plants with different color patterns by gene editing engineering.